The Isnad and Text Analysis of Narrative of seek knowledge even if it is in China, for seeking knowledge is a duty on every Muslim - GENÇ, MUSTAFA (SAKARYA UNIV, 2021)
There are many verses and hadiths that emphasize the virtue of knowledge and encourage learning. Muslim scholars, especially hadith scholars, have worked according to these divine inducements in the historical process, and had endured many arduous journeys for the sake of knowledge. Among the prevalent narratives widely spread in the context of incentive motives is the hadith of seek knowledge even if you have to go as far as China, for seeking knowledge is a duty on every Muslim. In this context, emphasis will be placed first on evaluating the authenticity of the hadith that was transmitted by many Companions in hadith the sources, and which was famous for the phrase seeking knowledge is an obligation on every Muslim. The origin of the narration that will be covered in the research is considered to be this hadith. Thus, the research indicates that one of the Companions who narrated this hadith is Anas ibn Malik, and the hadith narrated from him both included the phrase of seek knowledge even in China in some of its narrations, and in others it was narrated without that phrase. In this respect, the focus will be on how, through which narrators, and for what purpose this phrase is added in the text. The narration is also will be analyzed in chain and text by identifying points of contact between the variants related to the narration.
Keywords: Hadith; Knowledge; China; Narration; Variant; Singularity; Interpolation